Growing old together: Compassionate love and health in older adulthood. (August 2014) - Rauer, Amy J.; Sabey, Allen; Jensen, Jakob F.
The health benefits associated with marriage are disproportionately large in older adulthood, due in part to the powerful role spouses play in promoting each other's well-being. What remains unclear is what motivates this caretaking. To determine whether compassionate love plays a role, the current study used an Actor–Partner Interdependence Model to examine how 64 older couples' compassionate love is linked to their health. Feeling compassionate love was linked to better health for wives. The partner effects, however, painted a more complicated picture, with the receipt of compassionate love appearing to undermine health. Given the unprecedented growth in the number of older adults in the United States, we have a vested interest in determining how compassionate love may help or hinder well-being in later-life marriages.